2010
DOI: 10.1111/j.1745-4603.2010.00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' Creaminess Concept Perception: A Cross‐cultural Study in Three Spanish‐speaking Countries

Abstract: Creaminess is a complex sensory attribute that is critical for consumer liking in a wide range of products. For this reason, it is crucial to understand consumers' expectations when trying a creamy product. The aim of the present work was to study consumers' creaminess perception in three different Spanish-speaking countries. Between 107 and 120 consumers were recruited from Argentina, Spain and Uruguay. Participants were asked to provide a definition of creaminess and to list all the creamy products they knew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 27 publications
1
15
0
1
Order By: Relevance
“…However, it was possible to note that several other terms were used by the consumers to express the attribute texture as "cremosity" and "firmness" confirming previous studies, that reported the existence of such assorted words to express this attribute (Antmann et al, 2012;Antmann et al, 2011a, b). Furthermore, consumers' attitude towards sensory evaluation depends on their memory structure, which is definitely related to their personal characteristic (Varela et al, 2013).…”
Section: Accepted Manuscriptsupporting
confidence: 64%
“…However, it was possible to note that several other terms were used by the consumers to express the attribute texture as "cremosity" and "firmness" confirming previous studies, that reported the existence of such assorted words to express this attribute (Antmann et al, 2012;Antmann et al, 2011a, b). Furthermore, consumers' attitude towards sensory evaluation depends on their memory structure, which is definitely related to their personal characteristic (Varela et al, 2013).…”
Section: Accepted Manuscriptsupporting
confidence: 64%
“…In order to obtain a clearer vision of consumers' creaminess perception and particularly of the results of the present work, it is interesting to compare the results with those reported by Antmann et al (2010). In that study, Spanish and Uruguayan consumers were asked to define creaminess using their own words.…”
Section: Resultsmentioning
confidence: 87%
“…Projection techniques have been used with participants from Spain, Argentina, and Uruguay. Using word association tasks, the consumers were asked to write down the first four words, descriptions, associations, thoughts, or feelings that came to mind when thinking of creaminess (Antmann et al, 2011b). The consumers mainly associated creaminess with creamy food products and with texture, flavor, and appearance attributes such as smoothness, softness, sweetness, and pleasantness.…”
Section: Downloaded By [University Of Connecticut] At 19:53 11 Octobementioning
confidence: 99%